Impact of admitting department on the management of acute coronary syndrome after an out of hospital cardiac arrest - Jansky, Pavel; Motovska, Zuzana; Kroupa, Josef; Waldauf, Petr; Kafka, Petr; Knot, Jiri; Jarkovsky, Jiri (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
AIM: This study aimed to analyze the influence of the hospital admitting department on adherence to the Guidelines of European Society of Cardiology for management of acute coronary syndromes in patients after out-of-hospital cardiac arrest (OHCA) of coronary etiology. METHODS: We studied retrospective-prospective register of 102 consecutive patients with OHCA as a manifestation of acute coronary syndrome (ACS). Patients were admitted to the coronary care unit (CCU) 52, general intensive care unit (GICU) 21, or GICU after initial Cath lab treatment (CAG-GICU) 29. This study compared the differences in the management of ACS in patients with OHCA of coronary etiology based on the admitting department in a tertiary care institution. RESULTS: Twelve of the 21 (57.1%) patients admitted to the GICU were evaluated as having ACS on-site where they experienced OHCA. In the CCU group, 50 out of 52 (96.2%) and 28 of 29 (100%) patients in the CAG-GICU group (P<0.001). Coronary angiography was performed in 10 of 21 patients (48%) admitted to the GICU. It was performed in 49 out of 52 (94%) CCU patients and, in the CAG-GICU group, 28 out of 29 patients. The mean time to CAG differed significantly across groups (that is, GICU 200.7 min., CCU 71.2 min., and CAG-GICU 7.5 min. (P<0.001)). Aspirin was used in 48% of GICU, 96% of CCU, and 79% of CAG-GICU patients (P<0.001), while in the pre-hospital phase, aspirin was used in 9.5% of GICU, 71.2% of CCU, and 50% of CAG-GICU patients (P<0.001). P2Y12 inhibitor prescriptions were lower in patients admitted to the GICU (33% vs. 89% CCU and 57% CAG-GICU, P<0.001). The department's choice significantly affected the time to initiation of antithrombotics, which was the longest in the GICU. CONCLUSION: The choice of admission department for patients with OHCA caused by ACS was found to affect the extent to which the recommended treatments were used. An examination of OHCA patients by a cardiologist upon admission to the hospital increased the likelihood of an early diagnosis of ACS as the cause of OHCA.
Keywords: coronary angiography; Humans; koronární angioplastika; lidé; Acute Coronary Syndrome; přijímací oddělení nemocnice; koronární angiografie; out-of-hospital cardiac arrest; general intensive care unit; Retrospective Studies; antithrombotic therapy; acute coronary syndrome; Aspirin; Coronary Angiography; zástava srdce mimo nemocnici; Percutaneous Coronary Intervention; Out-of-Hospital Cardiac Arrest; Admitting Department, Hospital; retrospektivní studie; coronary care unit; akutní koronární syndrom